Evaluation Of Multi-Fuel Hybrid Engine Performance Using Gas Turbine Simulation Program - Nekmat, Hafriz Najmi (Universiti Sains Malaysia, 2021)
This project paper presents the evaluation of multi-fuel hybrid engine performance with different types of fuels using the Gas Turbine Simulation Program (GSP). The multi-fuel hybrid engine is a modern engine design with many new technologies such as contra-rotating fan, a dual-combustion sequential system and a Cryogenic Bleed Air Cooling System (CBACS). A latest study shows the performance assessment of the multi-fuel hybrid engine by using two types of fuels which are Liquified Natural Gas (LNG) and kerosene. Biofuels such as Camelina Bio-Derived Synthetic Paraffinic Kerosene (BSPK), Jatropha BSPK and Hydro-processed Ester and Fatty Acid (HEFA) are the fuel that are used in evaluating the multi-fuel hybrid engine performance in this study. In addition to evaluating the effect of fuel properties on the engine, the engine performance and emissions are compared with the multi-fuel hybrid engine with hydrogen. The first part of this study is biofuels are combusted in the second combustor which is the inter-stage turbine burner (ITB) replacing kerosene. Hydrogen is combusted in the main combustor replacing LNG for the second part of this study. From the result obtained, the MFHE with hydrogen gives the best performance in the most aspects and is proven in reducing the emission of Nitrogen Oxide (NOx).